2023
DOI: 10.1021/acs.analchem.3c02831
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Enzyme-Activatable Spherical Nucleic Acids for Spatiotemporally Controlled Signal Amplification Molecular Imaging and Combinational Tumor Therapy

Youhui Zeng,
Ruiying Peng,
Yingcai Hu
et al.

Abstract: Due to the adjustable hybridization activity, antinuclease digestion stability, and superior endocytosis, spherical nucleic acids (SNAs) have been actively developed as probes for molecular imaging and the development of noninvasive diagnosis and image-guided surgery. However, since highly expressed biomarkers in tumors are not negligible in normal tissues, an inevitable background signal and the inability to precisely release probes at the chosen region remain a challenge for SNAs. Herein, we proposed a ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Zhang constructed a polymer SNA structure with the SNA shell containing antisense oligonucleotides targeting MC1R and prodrug inhibitors of tyrosinase, which successfully reduced melanin production in melanoma cells. 46 Zheng developed a polymer SNA with antisense oligonucleotides and an amphiphilic self-assembling polymer as the core, 79 which efficiently loaded nanoprobes and Dox. After treatment, the quantitative average fluorescence intensity was calculated to be 1.51-fold higher than that of nontumoral sites.…”
Section: Amplification Of the Structure And Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang constructed a polymer SNA structure with the SNA shell containing antisense oligonucleotides targeting MC1R and prodrug inhibitors of tyrosinase, which successfully reduced melanin production in melanoma cells. 46 Zheng developed a polymer SNA with antisense oligonucleotides and an amphiphilic self-assembling polymer as the core, 79 which efficiently loaded nanoprobes and Dox. After treatment, the quantitative average fluorescence intensity was calculated to be 1.51-fold higher than that of nontumoral sites.…”
Section: Amplification Of the Structure And Capacitymentioning
confidence: 99%
“…Zheng engineered an endogenous APE1 enzyme-activated SNA nanosensor for spatiotemporal signal amplification molecular imaging and combined cancer therapy. 79 This intelligent Ep-SNA@Dox nanosensor, containing DNA hairpins with AP sites, ASOs, and Dox, can be specifically cleaved by APE1 in tumor cells, enabling high-sensitivity imaging of mRNA and drug release. In vitro and in vivo experiments demonstrated that this nanosensor not only possesses high-sensitivity imaging capability for target molecules but also enables precise drug release, offering a new approach to combined therapy.…”
Section: Scale-up Of Therapeutic Modalitiesmentioning
confidence: 99%
“…To meet the urgent need for ultrasensitivity in miRNA detection strategies, researchers have developed various miRNA detection methods based on isothermal amplification technologies. Thereinto, enzyme-free isothermal amplification strategies, such as hybridization chain reaction, strand displacement reaction, entropy-driven reaction, and catalytic hairpin assembly (CHA), , are easier to apply in biomolecular analysis. As a powerful DNA amplification technique, CHA can induce the binding of two DNA hairpins to produce a large quantity of double-stranded DNA structures through the catalytic action of a primer strand.…”
Section: Introductionmentioning
confidence: 99%
“…9 Spherical nucleic acids (SNA) have been designed to be used in combination therapy with gene silencing and CDT while allowing visualization of tumor-associated survivin mRNA levels to provide feedback on the effectiveness of the therapy. 10 BP (black phosphorus)-based synergistic nanoprobes (BP/CD (carbon nanodots)/Au/Dox (doxorubicin)) not only enable the combined treatment of PTT/PDT (photodynamic therapy)/chemotherapy, but also provide feedback on specific targets in tumor tissue. 11 Notably, recent developments in oncology have highlighted the effectiveness of ferroptosis and immune checkpoint blockade (ICB).…”
Section: ■ Introductionmentioning
confidence: 99%